A randomised, multi-centre, prospective, observer and patient blind study to evaluate a non-absorbable polypropylene mesh vs. a partly absorbable mesh in incisional hernia repair - Rickert, Alexander Lothar; Kienle, Peter; Büchler, Markus W. (Langenbeck's archives of surgery, 2012)
BACKGROUND: The implantation of a polymer mesh is considered as the standard treatment for incisional hernia. It leads to lower recurrence rates compared to suture techniques without mesh implantation; however, there are also some drawbacks to mesh repair. The operation is more complex and peri-operative infectious complications are increased. Yet it is not clear to what extent a mesh implantation influences quality of life or leads to chronic pain or discomfort. The influence of the material, textile structure and size of the mesh remain unclear. The aim of this study was to evaluate if a non-absorbable, large pore-sized, lightweight polypropylene (PP) mesh leads to a better health outcome compared to a partly absorbable mesh. METHODS/DESIGN: In this randomised, double-blinded study, 80 patients with incisional hernia after a median laparotomy received in sublay technique either a non-absorbable mesh (Optilene® Mesh Elastic) or a partly absorbable mesh (Ultrapro® Mesh). Primary endpoint was the physical health score from the SF-36 questionnaire 21 days post-operatively. Secondary variables were patients' daily activity score, pain score, wound assessment and post-surgical complications until 6 months post-operatively. RESULTS: SF-36, daily activity and pain scores were similar in both groups after 21 days and 6 months, respectively. No hernia recurrence was observed during the observation period. Post-operative complication rates also showed no difference between the groups. CONCLUSION: The implantation of a non-absorbable, large pore-sized, lightweight PP mesh for incisional hernia leads to similar patient-related outcome parameters, recurrence and complication rates as a partly absorbable mesh.